The role of tarung derajat extracurricular activities in shaping students’ character - Khasanah, Nurul; Susanto, Indra Himawan; Mustar, Yetty Septiani; Nugraha, Testa Adi (Sriwijaya Journal of Sport, 2026)
Research Objectives: Strengthening character education is an important goal in schools and can be supported through non-academic activities, including martial arts–based extracurricular programs. Tarung Derajat, as a form of martial arts training, is believed to contribute to the development of positive character values such as discipline, responsibility, sportsmanship, and cooperation among students. Research Objectives: This study aims to analyze the role of Tarung Derajat extracurricular activities in shaping students’ character, particularly in the aspects of discipline, responsibility, sportsmanship, and cooperation at SMA Negeri 1 Sekaran, Lamongan Regency. Methods: This research employed a mixed-methods approach using an explanatory sequential design. Quantitative data were collected through questionnaires distributed to 30 students participating in the Tarung Derajat extracurricular program. Qualitative data were obtained through interviews with key informants, including the vice principal for student affairs, a physical education teacher, the Tarung Derajat coach, and participating students. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using thematic analysis. Results: The quantitative analysis showed that students’ character levels in the four aspects—discipline, responsibility, sportsmanship, and cooperation—were categorized as high. These findings were supported by qualitative data indicating that consistent training, mental development, and the values embedded in Tarung Derajat activities contributed positively to students’ character formation. Conclusion: Tarung Derajat extracurricular activities play a strategic role in supporting character education among students. Therefore, schools are encouraged to continuously optimize and sustain the implementation of such extracurricular programs to further strengthen students’ character development.